2021
DOI: 10.1186/s12957-021-02450-9
|View full text |Cite|
|
Sign up to set email alerts
|

Long-term oncologic safety of immediate reconstructive surgery in patients with invasive breast cancer: a retrospective matched-cohort study

Abstract: Objective Immediate reconstruction (IR) is a safe and effective surgical treatment for patients with breast cancer. We aimed to assess the prognosis, aesthetic outcomes, and patient satisfaction of IR compared with breast conservation surgery (BCS) and total mastectomy (TM). Methods This retrospective matched-cohort study was conducted between May 2005 and December 2014. We established two cohorts according to the tumor (T) size of breast cancer. I… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Yi et al (66) found no significant difference in the DFS between the two groups after adjusting for the clinical TNM staging. A study by Song et al (67) showed that in patients with tumor sizes greater than 3 cm, the DFS of the MT group was higher than the MT+IR group, especially in HER2-positive and triple-negative patients. We performed subgroup analyses of propensity-matched studies that were matched for age, clinical stage, molecular type, and response to NAC (40)(41)(42)44).…”
Section: Discussionmentioning
confidence: 99%
“…Yi et al (66) found no significant difference in the DFS between the two groups after adjusting for the clinical TNM staging. A study by Song et al (67) showed that in patients with tumor sizes greater than 3 cm, the DFS of the MT group was higher than the MT+IR group, especially in HER2-positive and triple-negative patients. We performed subgroup analyses of propensity-matched studies that were matched for age, clinical stage, molecular type, and response to NAC (40)(41)(42)44).…”
Section: Discussionmentioning
confidence: 99%